No amor e na dor: famílias que convivem com a esquizofrenia em seu lar - Schühli, Patricia Aparecida Pedro (2009)
A comprehension of the caretaking family which lives with the schizophrenic subject is provided. This is coupled to the manner the whole historical process of a surrogate network affects their practices in their day-to-day care in the family. Current exploratory, descriptive and qualitative research was undertaken with eight relatives of schizophrenia-diagnosed patients (F20 of CID-10), outpatients of a psychiatric asylum whose treatment and follow-up were carried out at the Center for Psychosocial Attendance (CAPS III of Cascavel PR Brazil) since 2006 when the service started, and who accepted to participate in the research. The project was approved by the Permanent Committee in Research Ethics in Humans of the State University of Maringá, registered under 113/2009. Data were collected between March and May 2009 by means of an interview with the following monitoring question: How can you cope ... with schizophrenia in your home? The question sought a meaning beyond living and helped the researcher to clarify the meanings that relatives gave within the context of the proposed theme. Registers were undertaken by recorder and field notes in which the behavior, attitudes and expression manners in each encounter were jotted down so that such information may deepen the interpretation given. Bardin's content analysis technique was employed for data analysis. Dialogues were transcribed in full so that the three proposed phases which constituted the content analysis: pre-analysis, investigation of material and inference/interpretation, could be investigated. Through register units or their components two categories could be perceived in the interpretation of the deponents' dialogues: Schizophrenia: a stranger who invaded my home and Ups and Downs of caretaking of the schizophrenic subject in the family day-to-day experience. Results show that the family experience with the schizophrenic subject is experienced within a context pervaded by many occurrences. Relatives associate caretaking with suffering and that these issues make difficult the caretaking process. Lack of family support, bias and lack of hope are highlighted in such coliving, leading towards a sentiment of failure and of physical and emotional wastage. Results show that health professional may help these subjects to recover their moral esteem in so far as they are beings-in-the-world, and prepare them to face their existential conditions through the construction of an authentic experience.